Learning and Earning: Evidence from a Randomized Evaluation in India - Pushkar Maitra; Subha Mani (Institute for the Study of Labor (IZA), 2014)
This paper presents the treatment effects from participating in a subsidized vocational training program targeted at women residing in low-income households in India. We combine pre-intervention data with two rounds of post-intervention data from a randomized field experiment to quantify the 6- and 18-month treatment effects of the program. The 6-month effects of the program indicate that women who were offered the training program are 6 percentage points more likely to be employed, 4 percentage points more likely to be self-employed, work 2.5 additional hours per week, and earn 150 percent more per month than women in the control group. Using a second round of follow-up data collected 18 months after the intervention, we find that the 6-month treatment effects are all sustained over this period. Our findings indicate credit constraints, distance, and lack of proper child care support as important barriers to program completion. Further, we also rule out two alternative mechanisms signalling and behavior that could drive these findings. Finally, a simple cost-benefit analysis suggests that the program is highly cost-effective.
Keywords: I21; J19; J24; O15; 330; vocational training; panel data; India; economic returns; field experiment